First reported case of fascia lata sling in stress urinary incontinence in Peru - Salazar Rengifo, Orlando (2023)
Stress urinary incontinence is common in women from middle adulthood onwards.The most frequent technique to treat these cases is the synthetic sling. However,the autologous sling has good results comparable with the synthetic material in thevarious studies published. We present a case treated with fascia lata sling, describingthe technique and evolution.